Multi-period optimal energy procurement and demand response in smart grid with uncertain supply - Libin Jiang; Low, S. (2011 50th IEEE Conference on Decision and Control and European Control Conference, 2011)
We propose a simple model that integrates two-period electricity markets, uncertainty in renewable generation, and real-time dynamic demand response. A load-serving entity decides its day-ahead procurement to optimize expected social welfare a day before energy delivery. At delivery time when renewable generation is realized, it sets prices to manage demand and purchase additional power on the real-time market, if necessary, to balance supply and demand. We derive the optimal day-ahead decision, propose real-time demand response algorithm, and study the effect of volume and variability of renewable generation on the social welfare.